On the generalized mass transport equation to the concept of variable fractional derivative - Atangana, Abdon; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
The hydrodynamic dispersion equation was generalized using the concept of variational order derivative. The modified equation was numerically solved via the Crank-Nicholson scheme. The stability and convergence of the scheme in this case were presented. The numerical simulations showed that, the modified equation is more reliable in predicting the movement of pollution in the deformable aquifers, than the constant fractional and integer derivatives.